Factors associated with using research evidence in national sport organisations - Holt, N. L.; Pankow, K.; Camiré, M.; Côté, J.; Fraser-Thomas, J.; MacDonald, D. J. (Journal of Sports Sciences, 2018)
The purpose of this study was to explore factors associated with the use of research evidence in Canadian National Sport Organisations (NSOs). Data were collected via individual semi-structured interviews with 21 representatives from Canadian NSOs. A qualitative description approach was used. Interviews were transcribed verbatim and subjected to an inductive-to-deductive thematic analysis. A research implementation framework (Rycroft-Malone, 2004) was used to organise inductively derived themes into the higher-order categories of evidence (use of evidence, disconnection between research and practice), context (lack of capacity, organisational structure), and facilitation (personal connections with researchers and sport scientists, formal meetings with stakeholders). Overall, NSO representatives did not have a clear understanding of evidence and lacked capacity to access and translate research. However, some context factors, along with internal and external facilitators, were in place and could be used to enhance research implementation. Abstract from author